Origens e ramificações da artéria celiaca em fetos de suínos (Sus scrofa domesticus - Linnaeus, 1758) da linhagem “Rezende” - Gonçalez, Patrícia Orlandini (2001)
Thirty swine fetuses of the" Rezende " lineage , males and females were dissected, after the injection of the arterial vascular system, through thoracic descendens aorta artery. This injection was done with Neoprene latex " 450 " colored with specific pigment and fíxation in aqueous solution of formalin 10%, for observations of the origins and ramifications of the celiac artery. It was got these following results: the celiac arteiy was present in 96,66% of the cases, being original of the ventral portion of the abdominal descendens aorta artery. As colateral branches presented the caudal phrenic artery (96,66%), branch to the leffc adrenal gland (73,33%), muscular branch (43,33%), gastric branch (6,66%) and pancreatic branch (3,33%). As terminal branches presented the hepatic artery (96,66%), lienal artery (96,66%) and left gastric artery (20,00%). The left gastric artery emitted directly the esophageal branch (60,00%), pancreatic branch (43,33%) and diverticular artery (3,33%). The lienal artery emitted directly the left gastric artery (80,00%), the diverticular artery (96,66%), left gastroepiploic artery (100,00%), gastrolienal branch (100,00%), pancreatic branch (76,66%) and gastric branch (3,33%). The hepatic artery emitted directly the gastroduodenal artery (100,00%), that became separated in cranial pancreaticoduodenal artery and right gastroepiploic artery, right gastric artery (100,00%), pancreatic branch (100,00%), left branch (60,00%), right branch (56,66%), gastric branch (10,00%) and pyloric branch (3,33%). In all the cases, the hepatic artery supplied direct or indirectly, lateral and mediai right branches, lateral and mediai left branches, artery o f the caudate lobe and cystic artery. In 1 case, the celiac artery was not present, and the lienal and hepatic arteries had direct origin in the abdominal descendens aorta artery. Anastomosises were observed between right and left gastroepiploic arteries (100,00%), duodenal branches from cranial and caudal pancreaticoduodenal arteries, right gastric artery and left gastroepiploic artery (16,66%), gastrolienal branch and left gastroepiploic artery (3,33%) and between pancreatic branches (3,33%).